Objective assessment of counselling for fetal heart defects: an interdisciplinary multicenter study - Kovacevic, Alexander; Bär, Stefan; Starystach, Sebastian; Simmelbauer, Andreas; Elsässer, Michael; Müller, Andreas; Mohammadi Motlagh, Aida; Oberhoffer-Fritz, Renate; Ostermayer, Eva; Ewert, Peter; Gorenflo, Matthias; Wacker-Gußmann, Annette (Journal of Clinical Medicine, 2020)
The objective of this study was to analyze parental counselling for fetal heart disease in an interdisciplinary and multicenter setting using a validated questionnaire covering medical, sociodemographic, and psychological aspects. n = 168 individuals were recruited from two pediatric heart centers and two obstetrics units. Overall, counselling was combined successful and satisfying in >99%; only 0.7% of parents were dissatisfied. “Perceived situational control” was impaired in 22.6%. Adequate duration of counselling leads to more overall counselling success (r = 0.368 ***), as well as providing written or online information (57.7% vs. 41.5%), which is also correlated to more “Transfer of Medical Knowledge” (r = 0.261 ***). Interruptions of consultation are negatively correlated to overall counselling success (r = −0.247 **) and to “Transparency regarding the Treatment Process” (r = −0.227 **). Lacking a separate counselling room is associated with lower counselling success for “Transfer of Medical Knowledge” (r = 0.210 ***). High-risk congenital heart disease (CHD) is correlated to lower counselling success (42.7% vs. 71.4% in low-risk CHD). A lack of parental language skills leads to less overall counselling success. There is a trend towards more counselling success for “Transfer of Medical Knowledge” after being counselled solely by cardiologists in one center (r = 0.208). Our results indicate that a structured approach may lead to more counselling success in selected dimensions. For complex cardiac malformations, counselling by cardiologists is essential. Parental “Perceived Situational Control” is often impaired, highlighting the need for further support throughout the pregnancy.